Systematic review of sensory-based interventions for children and youth (2015–2024) - Piller, Aimee; McHugh Conlin, Jessica; Glennon, Tara J.; Andelin, Lauren; Auld-Wright, Kelly; Teng, Krysti; Tarver, Talicia (Frontiers in Pediatrics, 2025)
IntroductionChildren with developmental disorders often benefit from interventions supporting participation, including sensory interventions, which should be grounded and informed by evidence. The purpose of this systematic review was to evaluate and summarize current evidence on the effectiveness of sensory-based interventions (SBIs) on functional outcomes to guide interventions.MethodsSearches were performed in Medline (OVID), CINAHL Complete, PsycINFO, OTSeeker, Cochrane Reviews, and ERIC. Inclusion criteria included the following: published in English between May 2015 and January 2024; participants aged 0–21 years with sensory integration/processing challenges; level I and II studies as classified by Johns Hopkins Nursing Evidence-Based Practice Model; functional outcomes indicated. The review followed the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analyses.ResultsTwenty-one studies were included. Strong strength of evidence supported use of deep pressure tactile input and caregiver training on the use of sensory strategies. Moderate strength of evidence supported that alternative seating did not improve attention. Additionally moderate strength of evidence supported targeting a variety of sensory systems is more effective than targeting only one system. There is a lack of evidence on the impact of sensory environmental modifications.DiscussionSBIs may be useful for improving functional outcomes and participation. Further research is needed to clarify effectiveness for specific outcomes.